LEGAL PROTECTION FOR READY-TO-EAT FOOD BUSINESS CONDUCT THROUGH HALAL PRODUCT GUARANTEES - Enny Martha Sasea (Awang Long Law Review, 2025)
Certification and Labeling of Halal Goods is a fatwa and information about halalness. a halal product and one form of state regulation that provides the widest possible choice to the public to consume halal goods based on the provisions of Law Number 8 of 1999 concerning Consumer Protection. The formulation in this study is legal protection for fast food business actors through halal product guarantees and Legal Sanctions for Fast Food Business Actors Who Violate Halal Product Regulations in Indonesia. The method used in this study is normative juridical. Legal protection for fast food business actors through halal product guarantees is very important to ensure that products circulating in the community are not only safe and healthy, but also in accordance with Islamic principles. Through various laws and regulations, both administrative and criminal, the state provides clear protection for business actors and consumers.